Pest categorisation of the non‐EU phytoplasmas of tuber‐forming Solanum spp. (23rd December 2020) - ,; Bragard, Claude; Dehnen‐Schmutz, Katharina; Gonthier, Paolo; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; Potting, Roel; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Plant Health performed a pest categorisation of four phytoplasmas of tuber‐forming Solanum spp. known to occur only outside the EU or having a limited presence in the EU. The only tuber‐forming species of Solanum reported to be phytoplasma infected is S. tuberosum . This opinion covers ' Candidatus Phytoplasma americanum', ' Ca . P. aurantifolia'‐related strains (GD32; St_JO_10, 14, 17; PPT‐SA; Rus‐343F; PPT‐GTO29, ‐GTO30, ‐SINTV; Potato Huayao Survey 2; Potato hair sprouts), ' Ca . P. fragariae'‐related strains (YN‐169, YN‐10G) and ' Ca . P. pruni'‐related strains (Clover yellow edge; Potato purple top AKpot7, MT117, AKpot6; PPT‐COAHP, ‐GTOP). Phytoplasmas can be detected by molecular methods and are efficiently transmitted by vegetative propagation. Phytoplasmas are also transmitted in a persistent and propagative manner by some insects belonging to families within Cicadomorpha, Fulgoromorpha and Sternorrhyncha (order Hemiptera). No transovarial, pollen or seed transmission has been reported. The reported natural host range of the phytoplasmas categorised here varies from restricted (' Ca . P. americanum', and ' Ca . P. fragariae'‐related strains) to wide (' Ca . P. aurantifolia'‐related strains and ' Ca . P. pruni'‐related strains), thus increasing the possible entry pathways in the latter case. S. tuberosum is widely cultivated in the EU. All the categorised phytoplasmas can enter and spread through the trade of host plants for planting, and by vectors. Establishment of these phytoplasmas is not expected to be limited by EU environmental conditions. The introduction of these phytoplasmas in the EU would have an economic impact. There are measures to reduce the risk of entry, establishment, spread and impact. Uncertainties result from limited information on distribution, biology and epidemiology. All the phytoplasmas categorised here meet the criteria evaluated by EFSA to qualify as potential Union quarantine pests, and they do not meet all the criteria to qualify as potential regulated non‐quarantine pests, because they do not occur or are not known to be widespread in the EU.